Effects of transport processes to the deposition and quality of atmospheric pressure chemical vapour deposited graphene - Fatin Bazilah Fauzi (Kulliyyah of Engineering, International Islamic University Malaysia, 2021)
Until now, producing homogeneous chemical vapour deposited graphene with zero defects remains a challenge. The research on chemical aspects has been extensively explored either through experiments or computational studies. Given that it is a mass-transport limited process for atmospheric-pressure CVD (APCVD), the gas-phase dynamics and interfacial phenomena at the gas-solid interface (i.e., the boundary layer) is a crucial controlling factors. In this research, the importance of CVD fluid dynamics aspect was emphasised through fundamental studies at both gas-phase and gas-solid phase. As a preliminary study, an extensive review of available APCVD literature provided information on the relationship of graphene quality and its corresponding growth parameter. From these parameters, Reynolds number was calculated with the consideration that it is a ternary gas mixture. This was then compiled into a CH4-H2-Ar ternary plot which predicts the quality of graphene and Reynolds number at all gas compositions. Higher Reynolds number was found to be promising for high-quality graphene deposit which could be obtained at the gas composition range of ≤1% of CH4, ≤10% of H2, and ≥90% of Ar. Following this, a customised homogenous gas with properties similar to mixture of CH4, H2 and Ar was used in our computational fluid dynamics (CFD) of APCVD graphene. The in-depth details on gas-phase dynamics, interfacial phenomena, particularly the boundary layer and mass transport during the deposition process, were studied. Conditions, where gravity parameter is vital or could be safely neglected in CFD, was also determined. CFD model also allowed a close-up view of the boundary layer at the gas-solid interface. This was found to provide the most reasonable estimation of boundary-layer thickness formed on top of substrate for a bounded flow system like in a CVD. Higher Reynolds number formed thinner boundary layer. Consecutively, the relationship between the deposited graphene quality with Reynolds number, boundary-layer thickness and mass transport were explored. Calculated mass transport coefficient shows a good correlation to graphene thickness but not it's defect density which suggests that graphene defects are more dependent on factors other than fluid dynamics. At the highest Reynolds number of 84, few-layer graphene with monolayer ratio, I2D/IG of ∼0.67 and defect ratio, ID/IG of ∼0.45 was obtained. Wherein the quality of graphene improves when the ID/IG decreased by 90% and I2D/IG increased by 60%. Based on the experimental and computational studies, transport process was shown to have a vital role in the APCVD graphene growth.